Advanced control of bidirectional three-phase BEV charger with V2X technology. (27th May 2020) - Rachid, Aziz; Fadil, Hassan El; Lassioui, Abdellah; Giri, Fouad
In this paper, the control of a bidirectional three-phase BEV charger with vehicle-to-grid functionality is addressed. The charger structure is composed of two bidirectional power converters: a three-phase ac-dc converter and a dc-dc converter associated to an electric vehicle battery. The control objectives are the following: i) estimation of the battery SOC; ii) unity power factor during grid-to-vehicle (G2V); iii) adjusting the reactive power injected into the power grid during vehicle-to-grid (V2G); iv) dc-bus voltage regulation; and v) ensuring and safeguarding the battery charging and discharging process. To this end and based on the system modelling into dq coordinates, a nonlinear controller is designed. The fact is that the battery SOC is not accessible to measurement. Hence, a nonlinear observer is designed to estimate all state variables on the battery-side. The performances of the proposed controller are highlighted using theoretical analysis and numerical simulations, which clearly illustrate that all control objectives are achieved.